Cyclic ether and anhydride ring opening copolymerisation delivering new ABB sequences in poly(ester- alt -ethers) † - Kerr, RWF; Craze, AR; Williams, CK (Royal Society of Chemistry, 2024)
Poly(ester-alt-ethers) are interesting as they combine the ester linkage rigidity and potential for hydrolysis with ether linkage flexibility. This work describes a generally applicable route to their synthesis applying commercial monomers and yielding poly(ester-alt-ethers) with variable compositions and structures. The ring-opening copolymerisation of anhydrides (A), epoxides (B) and cyclic ethers (C), using a Zr(iv) catalyst, produces either ABB or ABC type poly(ester-alt-ethers). The catalysis is effective using a range of commercial anhydrides (A), including those featuring aromatic, unsaturated or tricyclic monomers, and with different alkylene oxides (epoxides, B), including those featuring aliphatic, alkene or ether substituents. The range of effective cyclic ethers (C) includes tetrahydrofuran, 2,5-dihydrofuran (DHF) or 1,4-bicyclic ether (OBH). In these investigations, the catalyst:anhydride loadings are generally held constant and deliver copolymers with degrees of copolymerisation of 25, with molar mass values from 4 to 11 kg mol−1 and mostly with narrow dispersity molar mass distributions. All the new copolymers are amorphous, they show the onset of thermal decomposition between 270 and 344 °C and variable glass transition temperatures (−50 to 48 °C), depending on their compositions. Several of the new poly(ester-alt-ethers) feature alkene substituents which are reacted with mercaptoethanol, by thiol–ene processes, to install hydroxyl substituents along the copolymer chain. This strategy affords poly(ether-alt-esters) featuring 30, 70 and 100% hydroxyl substituents (defined as % of monomer repeat units featuring a hydroxyl group) which moderate physical properties such as hydrophilicity, as quantified by water contact angles. Overall, the new sequence selective copolymerisation catalysis is shown to be generally applicable to a range of anhydrides, epoxides and cyclic ethers to produce new families of poly(ester-alt-ethers). In future these copolymers should be explored for applications in liquid formulations, electrolytes, surfactants, plasticizers and as components in adhesives, coatings, elastomers and foams.